Re-examining norms-diffusion: the EU, democracy and rival powers. Issue 3 (3rd April 2022) - Youngs, Richard
ABSTRACT: This article concludes the special issue by drawing out key points from the foregoing contributions and suggesting what these imply for the future analysis of EU-related norms diffusion.